Sequência didática com metodologias ativas e análise de erros: promovendo o letramento matemático na educação financeira - Duarte, Géssica Trindade Pereira (2024)
When we think of the field of Mathematics, we think of a variety of theories and complex calculations, which are taught through abstractions of fictitious problems12. This view of the field is mistaken, as mathematics involves solving real problems faced by citizens, using logical reasoning, critical and reflective thinking in various everyday situations13. Thus, Mathematical Literacy (ML) must be the main objective of Mathematics Teaching in the 21st century, a period in which critical thinking is even more necessary due to the diversity of information that is provided at all times14. Therefore, the following question is proposed: does the use of Didactic Sequences (DS) in the 8th grade of Elementary School favor ML in Financial Education (FE)? 15Through a pedagogical intervention type research, of a qualitative, exploratory and descriptive nature, the objective was to analyze the levels of ML before and after the application of a DS involving FE, that it is possible to infer about the effectiveness of DS involving active methodologies for the promotion of ML16. For data analysis and organization, the ML levels and Error Analysis were used17. As a result, DS was validated as a potential teaching instrument, and progress in ML levels was observed after the application of DS18. The research showed that the interventions provided autonomy, reflection and conscious decision-making in the face of a diversity of situations for the students participating in the research.